Visualizing the Research Performance of Jadavpur University during 2012-2021: - Rahman, Ziaur (Qualitative and Quantitative Methods in Libraries; Vol 11 No 1 (2022): March issue 2022, 2022)
The purpose of this study is to systematically analyze the development and trends in the scientific production and collaborative pattern of Jadavpur University (JU) faculties between 2012 and 2021. The study obtained data from the Web of Science Core Collection (WoSCC) and it employed Biblioshiny, Histcite, CiteSpace V, and ScientoPy tools to convert, process, visualize, mapping and evaluate the selected dataset. The review has been conducted applying Scientometric approach to recognize the research paper publication citations, prolific author’s linkage and collaborations, preferred journals for research publishing, frequently used author keywords and co-occurrence network, subject distribution, citation bursts, as well as trend topics investigated. The collaborations amongst the leading research organizations and groups are also investigated with co-citation and keywords co-occurrence analysis. The results showed the production of JU research and pattern of scholarly communication has risen significantly over the past ten years and has made a significant contribution to the scientific community. Das S., Ghosh S., and Chakraborty S. were observed to be relevant authors in this University. National level collaboration with the USA, England, and Spain was observed. 'RSC Advances,' 'Polyhedron,' and 'New Journal of Chemistry' were found the most influential. This research can assist in mapping the research output of universities and other educational institutions and make a paradigm for future studies of publication trends and academic performance.